AN ARCHITECTURAL ACCULTURATION OF BALINESE, DUTCH, AND CHINESE IN PURI AGUNG KARANGASEM - Wulan Sasmitha Rani; Ayu Sari Undari Yani; Viola Violita Ramdhan Supena; Adzra Ashila Zhafira; Larasati Vie; Santi Salayanti (DIMENSI (Journal of Architecture and Built Environment), 2022)
Bali is one of the many provinces of Indonesia with the most preserved cultural heritage. One form of these heritages is the architectural heritage. The traditional architecture of the Balinese people is still widely used and sometimes repurposed by their own people, mostly the Puris. A Puri is a building that was once used to be the residence of the royal families during their prime. The architecture of these Puris has distinct characteristics on its location, function, and typology of the building. A unique example of these Puris is the Puri Agung Karangasem, which has three cultures infused to its architecture. Apart from the obvious Balinese characteristics, there are also European and Chinese influence which can be proven by the Gedong Maskerdam, Bale Kambang, making it a treasured heritage not only for the Balinese people, but also for Indonesian people in general. This research is meant to explain and to give more insight into the architecture of Puri Agung Karangasem, which in result would present as a piece of knowledge to encourage the community to be more appreciative towards maintaining the traditional architecture of the Balinese people as a piece of important heritage. The method used for this research is the qualitative descriptive method. Focusing on the visual analysis of the architectural elements that are influenced by the different cultures, supported with previous related research and article.